2015
DOI: 10.1007/s10803-015-2385-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Correlates of Developmental Changes in Healthy and Autistic Boys

Abstract: This study investigated neurodevelopmental changes in sound processing by recording mismatch negativity (MMN) in response to various degrees of sound complexity in 18 mildly to moderately autistic versus 15 healthy boys aged between 6 and 15 years. Autistic boys presented with lower IQ and poor performance on a range of executive and social function measures when compared to their healthy counterparts. We found that MMN in response to duration deviants was less lateralized in the clinical group whereas larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…There is some evidence indicating that MMN to complex speech-like deviants or vowel/word change is reduced in children with ASD compared to typically developing children (Kuhl et al, 2005; Kujala et al, 2010; Ludlow et al, 2014). However, other studies have not reported such diagnostic differences (Ceponiene et al, 2003; Kasai et al, 2005; Oram Cardy et al, 2005; Weismuller et al, 2015), or have reported enhanced MMN amplitude to frequency deviants or affective prosody in ASD or Asperger’s syndrome compared to typically developing children (Korpilahti et al, 2007; Lepisto et al, 2005, 2006). In the studies of Lepisto and colleagues, increased MMN in ASD and Asperger’s syndrome was not found at the usual frontal electrodes (Fz) but rather only at parietal electrodes, possibly reflecting the MMN in primary auditory cortex and reinforcing that differences in the locations of recording electrodes may impact the ability to detect MMN abnormalities in ASD.…”
Section: Sensory Processing In Individuals With Asd and Fxsmentioning
confidence: 95%
See 4 more Smart Citations
“…There is some evidence indicating that MMN to complex speech-like deviants or vowel/word change is reduced in children with ASD compared to typically developing children (Kuhl et al, 2005; Kujala et al, 2010; Ludlow et al, 2014). However, other studies have not reported such diagnostic differences (Ceponiene et al, 2003; Kasai et al, 2005; Oram Cardy et al, 2005; Weismuller et al, 2015), or have reported enhanced MMN amplitude to frequency deviants or affective prosody in ASD or Asperger’s syndrome compared to typically developing children (Korpilahti et al, 2007; Lepisto et al, 2005, 2006). In the studies of Lepisto and colleagues, increased MMN in ASD and Asperger’s syndrome was not found at the usual frontal electrodes (Fz) but rather only at parietal electrodes, possibly reflecting the MMN in primary auditory cortex and reinforcing that differences in the locations of recording electrodes may impact the ability to detect MMN abnormalities in ASD.…”
Section: Sensory Processing In Individuals With Asd and Fxsmentioning
confidence: 95%
“…Reports on MMN in ASD are highly inconsistent. Some studies report larger MMN amplitude in children with ASD (Ferri et al, 2003; Kujala, 2007; Lepisto et al, 2005, 2006), whereas others report smaller (Abdeltawwab and Baz, 2015; Ludlow et al, 2014) or equal amplitudes compared to typically developing children (Dunn et al, 2008; Jansson-Verkasalo et al, 2003; Roberts et al, 2011; Seri et al, 1999; Weismuller et al, 2015). Given the scope of this review, only MMN amplitude data are considered here.…”
Section: Sensory Processing In Individuals With Asd and Fxsmentioning
confidence: 99%
See 3 more Smart Citations